The Article Text ANALISIS PENGARUH CAR, LDR, DAN NPL TERHADAP ROA PADA INDUSTRI PERBANKAN INDONESIA (2015-2024) - Iis Prihatin Fatmawati Fatmawati; Dita Agustina; Tatu Fadhilatul Karimah; Sunita Dasman (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2026)
This study aims to analyze the effect of the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non-Performing Loan (NPL) on Return on Assets (ROA) in the Indonesian banking industry. This research employs a quantitative approach using secondary data obtained from Indonesian Banking Statistics published by the Financial Services Authority (OJK) for the period 2015–2024, comprising 40 quarterly observations. The data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results of the classical assumption tests indicate that the residuals are normally distributed; however, autocorrelation was detected in the initial model and subsequently corrected using the Cochrane– Orcutt method. The findings show that CAR, LDR, and NPL simultaneously have a significant effect on ROA. Partially, CAR and LDR have a positive and significant effect on ROA, while NPL has a negative and significant effect on ROA. These results indicate that capital adequacy and effective credit distribution play an important role in enhancing banking profitability, whereas higher levels of non-performing loans tend to reduce financial performance. Keywords: Capital Adequacy Ratio, Loan to Deposit Ratio, Non-Performing Loan, Return on Assets, Banking